Towards a socio-ecological practice of mathematics teacher education - Alf Coles (Sociedad Española de Investigación en Educación Matemática, 2023)
This theoretical article is a response to UNESCO's call for a new social contract for education, in the context of mathematics teacher education. The article sets out four principles behind "socio-ecological" practices in mathematics education: not taking nature as a fixed background for concerns; avoiding the epistemological error of taking the individual as the unit of learning; questioning what is centred in our work; moving towards a dialogic ethics. The article considers the "what" and the "how" of mathematics teacher education, from this socio-ecological perspective. In terms of the "how", it is argued a dialogic ethics prompts attention to the potential for a mathematics teacher educator taking a "meta-perspective" in relationships with prospective teachers, recognising those prospective teachers as "teachers", from the start of a teacher education course. In contexts where the "what" of mathematics teacher education is highly constrained, the "how" of socio-ecological practices may still be possible to enact.